The likely impact of climate change on the biodiversity of Italian forests - Borghetti, M.; La Mantia, T.; Menozzi, P.; Piotti, a (Forest@ - Rivista di Selvicoltura ed Ecologia Forestale, 2012)
Keywords: 2012; 245-250; 9; Adaptation; biodiversità delle foreste italiane; Biodiversity; borghetti m; citation; climate change; climatico sulla; contents; FOREST; http; impact; it; Italy; la mantia t; menozzi p; online 2012-11-19; piotti a; probabili impatti del cambiamento; sisef; url; www

Tree biomass and deadwood density into aged holm oak (Sardinia) and beech coppices (Tuscany) - Bertini, G.; Fabbio, G.; Piovosi, M.; Calderisi, M. (Forest@ - Rivista di Selvicoltura ed Ecologia Forestale, 2012)
Keywords: 108-129; 2011; 2012; 9; accepted; aged coppice forest; beech; bertini g; calderisi m; citation; deadwood; densità di biomassa e; fabbio g; FOREST; Holm oak; http; in toscana; invecchiati di leccio in; it; jul 21; living woody biomass; mar 19; may 07; necromassa legnosa in cedui; online 2012-05-07; piovosi m; published online; received; sardegna e di faggio; sisef; url; wood decay; www

Observations on natural regeneration in grazed Holm oak stands in the Ogliastra province (Sardinia, Italy) - Bianchi, L.; Calamini, G.; Sioni, S. (Forest@ - Rivista di Selvicoltura ed Ecologia Forestale, 2011)
: Observations on natural regeneration in grazed Holm oak stands in the Ogliastra province (Sardinia, Italy). This paper deals with the effects of grazing pressure in two Holm oak (Quercus ilex) stands in Ogliastra (cen tral-eastern Sardinia, Italy), with particular reference to the interactions with the natural regeneration proces ses. There is a positive interaction (facilitation) between shrubs and seedlings of tree species, as observed in other similar studies carried out by the same authors in other areas of Sardinia. Rubus ulmifolius proved to be the most efficient shrub for the protection and growth of saplings; the other shrub species play a less marked facilitating role. Although the density of shrubs hosting Holm oak seedlings is fairly high, their age and small size confirm that the current grazing pressure is incompatible with any chance of growth of the sa plings and success of the natural regeneration. The conservation of these stands must therefore rely on the rationalisation of human activities through the exploitation of a whole range of resources.
Keywords: 103-112; 2011; 665; 8; accepted; bianchi l; calamini g; citation; dell; Facilitation process; FOREST; Grazing in Forest; Holm oaks stands; http; id; in boschi di leccio; it; jan 13; jul 19; may 26; natural regeneration; ogliastra; online 2011-07-19; osservazioni sulla rinnovazione naturale; php; published online; received; sardegna; show; sioni s; sisef; soggetti a pascolo; url; www

Plant neighbour identity matters to belowground interactions under controlled conditions. - Armas, Cristina; Pugnaire, Francisco Ignacio (PloS one, 2011)
Root competition is an almost ubiquitous feature of plant communities with profound effects on their structure and composition. Far beyond the traditional view that plants interact mainly through resource depletion (exploitation competition), roots are known to be able to interact with their environment using a large variety of mechanisms that may inhibit or enhance access of other roots to the resource or affect plant growth (contest interactions). However, an extensive analysis on how these contest root interactions may affect species interaction abilities is almost lacking.
The following values have no corresponding Zotero field: accession-num: 22114696
Keywords: biomass; citation; Ecosystem; Environment; Plant Development; Plant Roots; Plant Roots: growth & development; Species Specificity